Tornar-se professor e o exercício profissional: a consciência e a percepção docente acerca do magistério - Nascimento, Vinicius Pereira do (2024)
This study seeks to analyze how teachers perceive their own profession, from their training up to their teaching practice. This study was focused on a group of seven public school teachers in the city of São Paulo. They are all high school teachers whose experiences range from one to thirty years of teaching. The theoretical foundations that guide this dissertation are based on two references: (i) the critical theory of society, with the authors Theodor Adorno and Walter Benjamin. (ii) Education, with the theorists Maurice Tardif and Marieta Gouvêa Penna. The aim is to understand how their perception of teaching affects their practice. The method used in the research was the focus group, involving teachers from all three career stages and separated by years of teaching experience. The data obtained was analyzed and organized into thematic axes. The results showed that the way teachers perceive their teaching profession affects the way they practice their profession. This study also provides evidence of how length of time teaching can influence professional practice and the way teachers perceive their profession throughout their careers. The results obtained showed that teaching experience alone is not sufficient for the development of a perception and awareness regarding teaching profession; other factors also influence the construction of teaching identity